Building Applications and Components with Visual Basic .NET - Pattison, Ted; Hummel, Joe (Addison-Wesley Professional, 2003)
Praise for Building Applications and Components with Visual Basic .NET "Ted shows a great depth of knowledge all the way down to the underlying mechanics of .NET. The author's depth in certain areas, like Events and Delegates, makes this a very useful book." -- Gregory A. Beamer , Microsoft MVP "The content in Building Applications and Components with Visual Basic .NET is quite unique; I don't think any other book covers the OOP features in the detail as this book does. This book is a definitive guide for all VB developers looking to master OOP skills." -- Darshan Singh , Managing Editor, PerfectXML.com "As a whole, the book is excellent--clear, and concise enough while still giving all the necessary details." -- Gerard Frantz , Consultant "Ted does a good job explaining the various OOP concepts and the high-level view of the CLR and related concepts. I definitely learned some things about the CLR that I didn't know, and I found it a good read." -- Paul Vick , Technical Lead, Visual Basic .NET, Microsoft Corp. "When Ted's first book came out in 1998 I dashed to the bookstore in a Harry- Potter-esque frenzy. That book taught me everything I needed to know about VB6, COM, MTS, etc. Now five years later, I have the privilege of reviewing his new VB.NET book (and also counting Ted as a good friend). Ted has done it again: combining the deep experience he's gained in his years working with DevelopMentor with his strong grasp of all things .NET, Ted has given us a book that's as easy to read as it is deep, informative, and accurate. This is THE book you need if you want to go long with Visual Basic .NET. To quote my Amazon review of his first book: 'Thank you Ted, you've done us all a service by writing this great new volume on Visual Basic .NET and the .NET Framework.'" -- George Bullock , MSDN "As you move forward into the .NET Framework with Visual Basic .NET, you'll find the material in this book to be valuable." --From the Foreword by Rocky Lhotka Building Applications and Components with Visual Basic .NET is the Visual Basic developer's guide to the .NET framework and object-oriented programming. The authors introduce the basic architecture of the .NET Framework and explore Visual Basic .NET's new OOP features, the syntax required to use them, and the effect that syntax has on code behavior. Readers gain skills essential to creating well-designed applications and component libraries for the .NET Framework. Among the topics explored in depth are: Writ...